The Pi40 gene for durable resistance to rice blast and molecular analysis of Pi40-advanced backcross breeding lines - Suh, J.P.; Roh, J.H.; Cho, Y.C.; Han, S.S.; Kim, Y.G.; Jena, K.K. (Scientific Societies, 2009)
Rice blast severely reduces production in both irrigated and water-stressed upland ecosystems of tropical and temperate countries. Nearly 50 blast resistance genes have been identified and some of those are incorporated into several rice cultivars. However, most of the resistance genes break down in a few years because of their race specificity and the rapid change in pathogenicity of the blast fungus (Magnaporthe grisea). The objective of this study was to analyze advanced backcross breeding lines (ABL) possessing the gene Pi40 for durable rice blast resistance. In all, 4 resistant genotypes, 4 japonica cultivars, and 10 monogenic differential rice genotypes with some known resistance genes were bioassayed in the greenhouse using seven sequential plantings and 29 virulent M. grisea isolates of Korea. The genotypes with the Pi40 gene had <3% diseased leaf area, which was significantly below the disease threshold level of 40% considered for durable blast resistance. Moreover, the genotypes with the Pi40 gene expressed compatibility with only two to three virulent M. grisea isolates supporting durability of resistance, in contrast to susceptible cultivars with >50% diseased leaf area and 10 compatible isolates. Of the 10 known resistance genes tested, Piz-t, Piz-5, and Pi9 showed differential reactions to the pathogen isolates in seven plantings. Genotyping of the ABL with 260 simple sequence repeat (SSR) markers revealed rapid conversion toward recurrent parent genotypes with fewer donor chromosomal segments (5.3 to 14.5%). Our study based on a sequential testing and background selection of breeding lines with the resistance gene Pi40 provided valuable information for durable blast resistance breeding in rice.